Nanostructuring of Ba8Ga16Ge30 clathrates by sol–gel‐calcination/chemical‐reduction route. Issue 3 (11th December 2015) - Pacheco, V.; Görlitz, H.; Wagner‐Reetz, M.; Kasinathan, D.; Cardoso‐Gil, R.; Carrillo‐Cabrera, W.; Meier‐Kirchner, K.; Rosner, H.; Grin, Yu.
Abstract : Nanoparticles (NPs) of Ba8 Ga16 Ge30 clathrate‐I were synthetized via sol–gel‐calcination/chemical‐reduction route. A solution of the metallic cations was used to prepare an acryl‐amid‐based gel. The gel is dried and calcined to obtain nanocrystalline powders of precursor oxides. The oxides are reduced by reacting with CaH2 to produce the clathrate, which is embedded in a CaO matrix. CaO is removed by a washing step to obtain the clathrate NPs. The shape and size of the precursor oxide NPs can be modified by addition of complexing agents, surfactants or by varying the pH or the metal and surfactant concentration in the gel. Powder X‐ray diffraction and SAED patterns confirm the clathrate‐I‐type crystal structure of the products. SEM/TEM investigations show that the size and morphology of the oxides are retained in the clathrate NPs after the reduction. The clathrate NPs exhibit morphology of thin plates ∼300 × ∼300 nm 2 and thickness of ∼50 nm, or sphere‐like morphology with ∼200 nm diameter, depending on the sol–gel synthesis conditions. The clathrate NPs were compacted via spark plasma sintering (SPS) to pellets with 53–93 % of crystallographic density. The total thermal conductivity ( κ ) of the pellet with 93 % density shows a reduction of 25 % in comparison to the reported κ in bulk clathrate. Preliminary characterization of the Seebeck ( S ) and electrical resistivity ( R ) of the low density sample (53 %) indicates n‐type conduction and semiconductor behavior of the Ba8 Ga16 Ge30 clathrate‐I. The transport properties of Ba8 Ga16 Ge30 clathrate‐I with 3‐, 4‐ or 5‐layer slabs and [100] surface termination as well as of the bulk material were calculated by using the semi‐classical Boltzmann transport theory within the constant scattering approximation. Our results show an increase in S for the geometries with reduced dimensions in agreement with the experimental observations.